Innovation of Kasti Ball Slide Media on Students' Batting Abilities - Muhamad Sifa’ur Rohman; Nurman Ramadhan; Hasan Saifuddin (Gladi : Jurnal Ilmu Keolahragaan, 2026)
Kasti is co mmonly taught in elementary physical education; however, batting skills remain challenging for many students due to difficulties in timing, ball contact accuracy, and hit direction control. This study examined the effect of kasti ball slide media on students’ batting ability. A pre-experimental one-group pretest–posttest design was applied. Participants were 21 fourth-grade students at MI Darul Ma’wa in the 2025/2026 academic year, selected through total sampling. Batting performance was measured using a validated kasti batting skill test. The intervention was implemented across 10 instructional meetings by integrating the slide media into structured and progressive batting practice activities. Data were tested for normality using the Shapiro–Wilk test and analyzed using a paired-samples t-test to compare pretest and posttest scores. Results showed that the students’ mean batting score increased from 15.28 in the pretest to 22.33 in the posttest. The paired-samples t-test indicated a significant improvement after the intervention (Sig. 2-tailed = 0.000, p < 0.05). These findings suggest that kasti ball slide media has a significant effect and can be used as an alternative learning medium to improve elementary students’ batting skills in physical education lessons. Future studies are recommended to involve a control group, larger samples, and retention testing to strengthen evidence of effectiveness.